2008
DOI: 10.1096/fj.07-093963
|View full text |Cite
|
Sign up to set email alerts
|

A group B streptococcal pilus protein promotes phagocyte resistance and systemic virulence

Abstract: Group B Streptococcus (GBS) is a major cause of invasive bacterial infections in newborns and certain adult populations. Surface filamentous appendages known as pili have been recently identified in GBS. However, little is known about the role of these structures in disease pathogenesis. In this study we sought to probe potential functional role(s) of PilB, the major GBS pilus protein subunit, by coupling analysis of an isogenic GBS pilB knockout strain with heterologous expression of the pilB gene in the nonp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 49 publications
1
92
2
Order By: Relevance
“…A detailed investigation of the contribution of pili to biofilm formation concluded that PI-2a pili, but not PI-1 or PI-2b pili, mediate formation of biofilms on both abiotic and biotic surfaces (27). Another study, using the background of type III GBS strain NEM316, found no role for BP-2a (PilB) in resistance to phagocytosis and intracellular killing by macrophages, in contrast to earlier work (19,23). The same study concluded that PI-2a pili contributed to virulence in a neonatal infection model but not in adult mice.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…A detailed investigation of the contribution of pili to biofilm formation concluded that PI-2a pili, but not PI-1 or PI-2b pili, mediate formation of biofilms on both abiotic and biotic surfaces (27). Another study, using the background of type III GBS strain NEM316, found no role for BP-2a (PilB) in resistance to phagocytosis and intracellular killing by macrophages, in contrast to earlier work (19,23). The same study concluded that PI-2a pili contributed to virulence in a neonatal infection model but not in adult mice.…”
mentioning
confidence: 80%
“…Conflicting results have been reported on the function of GBS pili in resistance to phagocytic killing (19,23). To evaluate whether the PI-1 pilus plays a role in phagocytic resistance, we first assessed GBS internalization and intracellular survival in human monocyte-derived macrophages.…”
Section: Figmentioning
confidence: 99%
“…However, whereas in GBS and pneumococcus the pilus appears to contribute to virulence in systemic disease (4,24,25), the opposite was found in Streptococcus pyogenes, where, unexpectedly, the presence of the pilus promotes capture of the organism in extracellular traps, thereby reducing the virulence potential of the organism (10). From an epidemiological perspective, it is also unclear whether the pilus contributes to systemic virulence in pneumococcus, as there is no difference in prevalence of pilus genes in nasopharyngeal and invasive disease isolates (5).…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulatory capabilities have also been associated with pili. Those of S. pneumoniae have been shown to promote inflammatory cytokine release (29), while S. agalactiae pili confer resistance to phagocytic killing (378). The pili of S. pyogenes promote bacterial aggregation via binding to the salivary component gp340, a process that may lead to increased bacterial clearance (145).…”
Section: Pilimentioning
confidence: 99%